Hatchett’s Brown (Van Dyck Red) in Oil Paintings—The Rediscovery of a Forgotten Pigment: Identification and the Historical–Technological Context - Anna Klisińska-Kopacz; Justyna Olszewska-Świetlik (Heritage)
Hatchett’s Brown, also known as Van Dyck Rose, was a unique pigment used in the 19th century, discovered and described by Charles Hatchett in 1803. This article presents the results of research on the identification of this pigment in the works of Henryk Siemiradzki and a 17th-century painting that was overpainted in the 19th century. Advanced analytical techniques, such as XRF, SEM-EDS, and Raman spectroscopy, were used to analyze pigments from the painter’s palette and the paint layers. This study sheds light on the use of Hatchett’s Brown in painting and its potential impact on the interpretation of historical overpainting.